A shaping sheet for semiconductor wafer chamfering grinding wheel dressing and preparation method thereof

By using a plastic sheet made of resin composite grinding material, the resin-bonding agent grinding wheel is trimmed, which solves the problems of frequent wear and poor grinding effect of the grinding wheel, and achieves the effect of extending service life and improving processing stability.

CN119036312BActive Publication Date: 2025-03-21HANGZHOU XINYANKE SEMICON MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411525073.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-21
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing resin bonding agent grinding wheels are prone to wear during chamfering and precision grinding. The groove shape changes lead to frequent replacement, low processing efficiency and high cost, and the material is too hard and cracked, and the grinding is not thorough during grinding, which affects the wafer chamfering processing effect.

Method used

The shaping sheet made of resin composite abrasive material ensures the dressing effect of the material on the resin bonding agent grinding wheel, improves the grinding precision and extends the service life of the grinding wheel.

Benefits of technology

It effectively extends the service life of resin bonding agent grinding wheels, improves the stability of wafer chamfering processing, reduces manpower and material losses caused by replacing grinding wheels, and ensures the stability of the grinding effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119036312B_ABST
    Figure CN119036312B_ABST
Patent Text Reader

Abstract

The present invention provides a shaping sheet for semiconductor wafer chamfering grinding wheel dressing and a preparation method thereof, and relates to the technical field of resin grinding materials. The shaping sheet for semiconductor wafer chamfering grinding wheel dressing is made of a resin composite grinding material, and the resin composite grinding material is prepared by mixing a composite resin, a wetting agent, an auxiliary material, a modified corundum, and a graded particle size abrasive, wherein the modified corundum is obtained by mixing corundum particles with a particle size of 1-3 mm with acid-washed mullite particles and then calcining and crushing. The present invention overcomes the shortcomings of the prior art, and ensures the dressing effect of the material on the resin-bonded grinding wheel by combining various abrasives with resin, and ensures the fineness of the final grinding, thereby increasing the service life of the grinding wheel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resin grinding materials, and in particular to a shaping sheet for dressing a semiconductor wafer chamfering grinding wheel and a preparation method thereof. Background Art

[0002] Currently, the wafer chamfering process includes: chamfering rough grinding - chamfering fine grinding, wherein the chamfering fine grinding is performed using a resin bonded grinding wheel. The material of this grinding wheel is relatively soft and is prone to wear. After wear, the groove shape changes and it cannot be used. Therefore, the grinding wheel needs to be replaced frequently, resulting in low processing efficiency and is not economical due to the high price of the grinding wheel.

[0003] The direct replacement cost of the resin bond grinding wheel is high and will also cause great waste. Therefore, at this stage, certain grinding materials can be used to repair the groove shape of the deformed resin bond grinding wheel so that it can continue to perform wafer chamfering processing. This can effectively reduce the replacement frequency of the resin bond grinding wheel. However, when grinding the groove shape of the resin bond grinding wheel, if the material is too hard, it may cause cracks in the grinding wheel. If the material is too soft, it is easy to cause incomplete grinding, affecting the effect of subsequent wafer chamfering processing. Therefore, choosing resin-related materials and setting certain abrasives is a practical direction. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a shaping sheet for dressing semiconductor wafer chamfering grinding wheels and a preparation method thereof, which ensures the dressing effect of the material on the resin-bonded grinding wheel by combining various abrasives with resin, ensures the final grinding fineness, and increases the service life of the grinding wheel.

[0005] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:

[0006] A shaping sheet for dressing a semiconductor wafer chamfering grinding wheel, the shaping sheet is made of a resin composite abrasive material, and the resin composite abrasive material consists of the following materials in parts by weight: 20-35 parts of composite resin, 0.5-3 parts of wetting agent, 10-16 parts of auxiliary materials, 2-6 parts of modified corundum, and 30-40 parts of graded particle size abrasive; the modified corundum is obtained by mixing corundum particles with a particle size of 1-3 mm with acid-washed mullite particles, calcining them, and then crushing them; in the graded particle size abrasive, particles with a particle size of 10-30 μm account for 15%-25% of the total amount, particles with a particle size of 30-60 μm account for 40%-50% of the total amount, and the particle size of the remaining particles is 60-150 μm.

[0007] Preferably, the composite resin is polyimide resin, phenolic resin, and epoxy resin in a mass ratio of 3-5:4-6:1-2.

[0008] Preferably, the wetting agent is a mixture of any one or more of water glass, liquid phenolic resin, cresol, and dextrin liquid.

[0009] Preferably, the auxiliary material is a mixture of any one or more of chromium oxide, zinc sulfide, iron oxide and calcium fluoride.

[0010] Preferably, the graded particle size abrasive is obtained by mixing diamond, cubic boron nitride and silicon carbide in a mass ratio of 6-8:2-4:1-3.

[0011] Preferably, the preparation method of the modified corundum comprises the following steps:

[0012] S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 10-20 minutes, filtered, rinsed repeatedly with clean water for 2-3 times, and dried to obtain the pickled mullite particles for use;

[0013] S2. Add corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 1-3:1, homogenize by ultrasonication, filter, sinter at 1300-1350°C for 15-30 minutes, take out, grind and crush through a 120-mesh sieve to obtain modified corundum.

[0014] The method for preparing a shaping sheet for semiconductor wafer chamfering grinding wheel dressing comprises the following steps:

[0015] (1) The resin binder, wetting agent, auxiliary material, modified corundum, and graded particle size abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0016] (2) The mixed material is placed in a mold, pressed into shape by a hot press, and then cured in an oven to obtain a disc-shaped semi-finished product 1 having a circular hole in the middle;

[0017] (3) Paste films on both sides of the semi-finished product 1, and fill the middle circular hole with resin / plastic to fix it, so as to obtain the semi-finished product 2 for use;

[0018] (4) The semi-finished product 2 is subjected to vibration aging treatment to obtain a finished shaped sheet.

[0019] Preferably, in step (2), the temperature of the hot press molding is 150-250°C, the pressure is 300KN-1500KN, the holding time is 20min-60min, and the temperature of the oven curing is 150-250°C, and the curing time is 10-30h.

[0020] Preferably, the outer diameter of the semi-finished product 1 is 290-310 mm, 190-210 mm, and 140-160 mm, the inner diameter is 10-50 mm, and the thickness is 0.9-1.4 mm.

[0021] Preferably, in the step (3), when the semi-finished product 1 is pasted on both sides, the film on one side is a circular film with a diameter of 250-300 mm and a thickness of 0.04-0.1 mm; the film on the other side is a circular film or a regular polygonal film, and when it is a circular film, its diameter is 30-100 mm and its thickness is 0.04-0.1 mm; when it is a regular polygonal film, the diagonal length of the regular polygonal film is 30-100 mm and its thickness is 0.04-0.1 mm.

[0022] The present invention provides a shaping sheet for semiconductor wafer chamfering grinding wheel dressing and a preparation method thereof, which has the advantages of:

[0023] The present invention adopts composite resin material to compound abrasives with graded particle sizes and modified corundum, which effectively ensures the grinding effect of the resin bond grinding wheel after material processing. On the basis of ensuring effective grinding, the composite resin material is used to prepare a dressing sheet that can be directly installed on the production line. The edge of the shaping sheet is processed by a chamfering rough grinding wheel so that the edge of the shaping sheet appears in a shape complementary to the groove shape of the resin bond grinding wheel. Then, the deformed resin bond grinding wheel is ground and trimmed, so that the resin bond grinding wheel can continue to perform fine chamfering of semiconductor wafers, effectively extending the service life of the resin bond grinding wheel, ensuring the stability of the chamfering processing of semiconductor wafers, and reducing the loss of manpower and material resources caused by replacement. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram of the structure of a shaping sheet in an embodiment of the present invention;

[0025] In the figure: 1. Resin composite abrasive material; 2. Film; 3. Filling plastic. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The polyimide resin used in the following examples and comparative examples was purchased from Hangzhou Sumonte Technology Co., Ltd.; the phenolic resin was phenolic resin 2123 purchased from Jinan Dahui Chemical Technology Co., Ltd.; the epoxy resin was high-purity E44 epoxy resin purchased from Jining Zhongjian Chemical Co., Ltd.

[0028] Embodiment 1:

[0029] Preparation of resin composite abrasive materials:

[0030] (1) Preparation of modified corundum:

[0031] S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 10 minutes, filtered, rinsed repeatedly with clean water for 3 times, and then dried to obtain the pickled mullite particles for use;

[0032] S2, adding corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 1:1, homogenizing with 400W ultrasonic for 15 minutes, filtering, sintering at 1300°C for 30 minutes, taking out, grinding and crushing through a 120-mesh sieve to obtain modified corundum;

[0033] (2) Preparation of composite resin: polyimide resin, phenolic resin and epoxy resin are mixed in a mass ratio of 3:4:1 to prepare composite resin;

[0034] (3) Setting of graded particle size abrasive: diamond, cubic boron nitride and silicon carbide are mixed in a mass ratio of 7:3:2 to obtain abrasive, and then the particle size is screened, wherein the particles with a particle size of 10-30 μm account for 15-25% of the total amount, the particles with a particle size of 30-60 μm account for 40-50% of the total amount, and the particle size of the remaining particles is 60-150 μm;

[0035] (4) Prepare the materials according to the following mass proportions:

[0036] 20 parts of composite resin, 0.5 parts of water glass, 4 parts of zinc sulfide, 6 parts of calcium fluoride, 2 parts of modified corundum, and 30 parts of graded particle size abrasive;

[0037] (5) The resin binder, water glass, zinc sulfide, calcium fluoride, modified corundum, and graded particle size abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0038] (6) The mixed material is loaded into a mold, and the temperature is adjusted to 250°C, the pressure is 300KN, and the holding time is 60 minutes by a hot press to press and form it. Then, the temperature is set to 250°C in an oven and cured for 10 hours to obtain a resin composite abrasive material with a circular hole in the middle.

[0039] Embodiment 2:

[0040] Preparation of resin composite abrasive materials:

[0041] (1) Preparation of modified corundum:

[0042] S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 20 minutes, filtered, rinsed with clean water twice, and dried to obtain the pickled mullite particles for use;

[0043] S2, adding corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 3:1, homogenizing with 400W ultrasonic for 15 minutes, filtering, sintering at 1350°C for 15 minutes, taking out, grinding and crushing through a 120-mesh sieve to obtain modified corundum;

[0044] (2) Preparation of composite resin: polyimide resin, phenolic resin and epoxy resin are mixed in a mass ratio of 5:6:2 to prepare composite resin;

[0045] (3) Setting of graded particle size abrasive: black silicon carbide and green silicon carbide are mixed in a mass ratio of 4:3 to obtain abrasive, and then the particle size is sieved, among which particles with a particle size of 10-30 μm account for 25% of the total amount, particles with a particle size of 30-60 μm account for 50% of the total amount, and the particle size of the remaining particles is 60-150 μm;

[0046] (4) Prepare the materials according to the following mass proportions:

[0047] 35 parts of composite resin, 3 parts of cresol, 16 parts of chromium oxide, 6 parts of modified corundum, and 40 parts of graded particle size abrasive;

[0048] (5) The resin binder, wetting agent, auxiliary material, modified corundum, and graded particle size abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0049] (6) The mixed material is loaded into a mold, and the temperature is adjusted to 150°C, the pressure is 1500KN, and the holding time is 20minmin through a hot press to press and form it. Then, the temperature is set to 150°C in an oven and cured for 30h to obtain a resin composite abrasive material with a circular hole in the middle.

[0050] Comparative Example 1:

[0051] Preparation of resin composite abrasive materials:

[0052] (1) Preparation of composite resin: polyimide resin, phenolic resin and epoxy resin are mixed in a mass ratio of 3:4:1 to prepare composite resin;

[0053] (2) Setting of graded particle size abrasive: diamond, cubic boron nitride and silicon carbide are mixed in a mass ratio of 7:3:2 to obtain abrasive, and then the particle size is sieved, wherein the particles with a particle size of 10-30 μm account for 15-25% of the total amount, the particles with a particle size of 30-60 μm account for 40-50% of the total amount, and the particle size of the remaining particles is 60-150 μm;

[0054] (3) Prepare the materials according to the following mass proportions:

[0055] 20 parts of composite resin, 0.5 parts of water glass, 4 parts of zinc sulfide, 6 parts of calcium fluoride, 1 part of 120 mesh corundum powder, 1 part of 120 mesh mullite powder, 30 parts of graded particle size abrasive;

[0056] (4) The resin binder, water glass, zinc sulfide, calcium fluoride, 120 mesh corundum powder, 120 mesh mullite powder, and graded particle size abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0057] (5) The mixed material is loaded into a mold, and the temperature is adjusted to 250°C, the pressure is 300KN, and the holding time is 60 minutes by a hot press to press and form it. Then, the temperature is set to 250°C in an oven and cured for 10 hours to obtain a resin composite abrasive material with a circular hole in the middle.

[0058] Comparative Example 2:

[0059] Preparation of resin composite abrasive materials:

[0060] (1) Preparation of modified corundum:

[0061] S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 10 minutes, filtered, rinsed repeatedly with clean water for 3 times, and then dried to obtain the pickled mullite particles for use;

[0062] S2, adding corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 1:1, homogenizing with 400W ultrasonic for 15 minutes, filtering, sintering at 1300°C for 30 minutes, taking out, grinding and crushing through a 120-mesh sieve to obtain modified corundum;

[0063] (2) Preparation of composite resin: polyimide resin, phenolic resin and epoxy resin are mixed in a mass ratio of 3:4:1 to prepare composite resin;

[0064] (3) Abrasive setting: diamond, cubic boron nitride and silicon carbide are mixed in a mass ratio of 7:3:2 to obtain the abrasive, and then the particle size is sieved to control the particle size to 10-30 μm;

[0065] (4) Prepare the materials according to the following mass proportions:

[0066] 20 parts of composite resin, 0.5 parts of water glass, 4 parts of zinc sulfide, 6 parts of calcium fluoride, 2 parts of modified corundum, and 30 parts of abrasive;

[0067] (5) The resin binder, water glass, zinc sulfide, calcium fluoride, modified corundum and abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0068] (6) The mixed material is loaded into a mold, and the temperature is adjusted to 250°C, the pressure is 300KN, and the holding time is 60 minutes by a hot press to press and form it. Then, the temperature is set to 250°C in an oven and cured for 10 hours to obtain a resin composite abrasive material with a circular hole in the middle.

[0069] Comparative Example 3:

[0070] Preparation of resin composite abrasive materials:

[0071] (1) Preparation of modified corundum:

[0072] S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 10 minutes, filtered, rinsed repeatedly with clean water for 3 times, and then dried to obtain the pickled mullite particles for use;

[0073] S2, adding corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 1:1, homogenizing with 400W ultrasonic for 15 minutes, filtering, sintering at 1300°C for 30 minutes, taking out, grinding and crushing through a 120-mesh sieve to obtain modified corundum;

[0074] (2) Preparation of composite resin: polyimide resin, phenolic resin and epoxy resin are mixed in a mass ratio of 3:4:1 to prepare composite resin;

[0075] (3) Abrasive setting: diamond, cubic boron nitride and silicon carbide are mixed in a mass ratio of 7:3:2 to obtain the abrasive, and then the particle size is sieved to control the particle size to 30-60 μm;

[0076] (4) Prepare the materials according to the following mass proportions:

[0077] 20 parts of composite resin, 0.5 parts of water glass, 4 parts of zinc sulfide, 6 parts of calcium fluoride, 2 parts of modified corundum, and 30 parts of graded particle size abrasive;

[0078] (5) The resin binder, water glass, zinc sulfide, calcium fluoride, modified corundum and abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0079] (6) The mixed material is loaded into a mold, and the temperature is adjusted to 250°C, the pressure is 300KN, and the holding time is 60 minutes by a hot press to press and form it. Then, the temperature is set to 250°C in an oven and cured for 10 hours to obtain a resin composite abrasive material with a circular hole in the middle.

[0080] Comparative Example 4:

[0081] Preparation of resin composite abrasive materials:

[0082] (1) Preparation of modified corundum:

[0083] S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 10 minutes, filtered, rinsed repeatedly with clean water for 3 times, and then dried to obtain the pickled mullite particles for use;

[0084] S2, adding corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 1:1, homogenizing by ultrasonication, filtering, sintering at 1300°C for 30 minutes, taking out, grinding and crushing through a 120-mesh sieve to obtain modified corundum;

[0085] (2) Preparation of composite resin: polyimide resin, phenolic resin and epoxy resin are mixed in a mass ratio of 3:4:1 to prepare composite resin;

[0086] (3) Abrasive setting: diamond, cubic boron nitride and silicon carbide are mixed in a mass ratio of 7:3:2 to obtain the abrasive, and then the particle size is sieved to control the particle size to 60-150 μm;

[0087] (4) Prepare the materials according to the following mass proportions:

[0088] 20 parts of composite resin, 0.5 parts of water glass, 4 parts of zinc sulfide, 6 parts of calcium fluoride, 2 parts of modified corundum, and 30 parts of graded particle size abrasive;

[0089] (5) The resin binder, water glass, zinc sulfide, calcium fluoride, modified corundum and abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use;

[0090] (6) The mixed material is loaded into a mold, and the temperature is adjusted to 250°C, the pressure is 300KN, and the holding time is 60 minutes by a hot press to press and form it. Then, the temperature is set to 250°C in an oven and cured for 10 hours to obtain a resin composite abrasive material with a circular hole in the middle.

[0091] Detection:

[0092] The resin composite abrasive material was prepared according to the methods of the above-mentioned Examples 1-2 and Comparative Examples 1-4, and the specifications of the prepared resin composite abrasive material were controlled to be 304 mm in outer diameter, 20 mm in inner diameter, and 1.2 mm in thickness;

[0093] Each group of resin composite abrasive materials 1 is subjected to film treatment on both sides (for subsequent installation and fixation). The film 2 on one side is a circular film with a diameter of 250 mm and a thickness of 0.05 mm. The film 2 on the other side is also a circular film with a diameter of 50 mm and a thickness of 0.05 mm. The center of the resin composite abrasive material 1 is filled with filling plastic 3 for subsequent installation on the motor. After filming and plastic filling, vibration aging treatment is performed for 3 hours to obtain a plastic sheet (such as Figure 1 as shown).

[0094] 1. Install the shaping sheet on the production line of wafer chamfering processing, first use the chamfering rough grinding wheel to process the edge of the shaping sheet, so that the edge of the shaping sheet appears in a shape complementary to the groove shape of the resin bond grinding wheel, and then use the processed shaping sheet to correct the resin bond grinding wheel used for continuous processing and continue to grind the wafer chamfer (the speed of the resin bond grinding wheel during the chamfering grinding process is 3000r / min, the feed rate is 50um / r, and the resin bond grinding wheel used is TABERCS-10 grinding wheel). The chamfering surface bevel angle of the new resin bond grinding wheel is 11±0.5° when the first 10 semiconductor wafers are chamfered. The shaping sheets prepared by the above groups are used to dress the resin bond grinding wheel after use, and the values ​​of the chamfering processing of 10 semiconductor wafers after dressing are recorded. The specific results are shown in Table 1 below:

[0095] Table 1

[0096] It can be seen from the above table that the resin bonded grinding wheels trimmed with shaping sheets prepared in experimental groups 1 and 2 have better stability in semiconductor wafer chamfering, and the processing effect is basically the same as that of the new grinding wheels.

[0097] 2. Detect the wear of each group of shaping sheets relative to the resin bond grinding wheel. Use the resin bond grinding wheel to grind against each group of shaping sheets respectively, and detect the thickness of the shaping sheet consumed when the resin bond grinding wheel wears away 0.5mm (repeat the experiment 5 times for each group of shaping sheets). The specific results are shown in Table 2 below:

[0098] Table 2

[0099] It can be seen from the above table that the shaping sheets prepared with the materials of Example 1 and Example 2 have less wear than the resin bond grinding wheel and better wear stability, and can be used for subsequent multiple shaping.

[0100] And on the basis of the above experiments, according to the actual specifications of the resin bond grinding wheel, the outer diameter of the shaping sheet can be adjusted to three specifications of 290-310mm, 190-210mm, and 140-160mm, the inner diameter is 10-50mm, and the thickness is 0.9-1.4mm.

[0101] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A shaping sheet for dressing a semiconductor wafer chamfering grinding wheel, characterized in that: The shaping sheet is made of a resin composite abrasive material, and the resin composite abrasive material is composed of the following materials in parts by weight: 20-35 parts of composite resin, 0.5-3 parts of wetting agent, 10-16 parts of auxiliary materials, 2-6 parts of modified corundum, and 30-40 parts of graded particle size abrasive; The composite resin is a polyimide resin, a phenolic resin, and an epoxy resin in a mass ratio of 3-5:4-6:1-2; The modified corundum is prepared by mixing corundum particles with a particle size of 1-3 mm with acid-washed mullite particles, calcining them, and then crushing them; In the graded particle size abrasive, particles with a particle size of 10-30 μm account for 15-25% of the total amount, particles with a particle size of 30-60 μm account for 40%-50% of the total amount, and the particle size of the remaining particles is 60-150 μm; and the graded particle size abrasive is obtained by mixing diamond, cubic boron nitride, and silicon carbide in a mass ratio of 6-8:2-4:1-3; The wetting agent is a mixture of any one or more of water glass, liquid phenolic resin, cresol, and dextrin liquid; The auxiliary material is a mixture of any one or more of chromium oxide, zinc sulfide, iron oxide and calcium fluoride; The preparation method of the modified corundum comprises the following steps: S1. The mullite particles with a particle size of 10-30 mm are pickled with 13% hydrofluoric acid for 10-20 minutes, filtered, rinsed repeatedly with clean water for 2-3 times, and then dried to obtain the pickled mullite particles for use; S2. Add corundum powder with a particle size of 1-3 mm and acid-washed mullite particles into clean water at a mass ratio of 1-3:1, homogenize by ultrasonication, filter, sinter at 1300-1350°C for 15-30 minutes, take out, grind and crush through a 120-mesh sieve to obtain modified corundum.

2. A method for preparing the shaping sheet as claimed in claim 1, characterized in that: The preparation method comprises the following steps: (1) The resin binder, wetting agent, auxiliary material, modified corundum, and graded particle size abrasive are mixed evenly by a three-dimensional mixer to obtain a mixed material for use; (2) The mixed material is placed in a mold, pressed into shape by a hot press, and then cured in an oven to obtain a disc-shaped semi-finished product 1 having a circular hole in the middle; (3) Paste films on both sides of the semi-finished product 1, and fill the middle circular hole with resin / plastic to fix it, so as to obtain the semi-finished product 2 for use; (4) The semi-finished product 2 is subjected to vibration aging treatment to obtain a finished shaped sheet.

3. The preparation method according to claim 2, characterized in that: In the step (2), the temperature of the hot press molding is 150-250°C, the pressure is 300KN-1500KN, the holding time is 20min-60min, and the temperature of the oven curing is 150-250°C, and the curing time is 10-30h.

4. The preparation method according to claim 2, characterized in that: The outer diameter of the semi-finished product 1 is 290-310mm, 190-210mm, and 140-160mm, the inner diameter is 10-50mm, and the thickness is 0.9-1.4mm.

5. The preparation method according to claim 2, characterized in that: In the step (3), when the semi-finished product 1 is pasted on both sides, the film on one side is a circular film with a diameter of 250-300 mm and a thickness of 0.04-0.1 mm; the film on the other side is a circular film or a regular polygonal film. When it is a circular film, its diameter is 30-100 mm and its thickness is 0.04-0.1 mm. When it is a regular polygonal film, its diagonal length is 30-100 mm and its thickness is 0.04-0.1 mm.

Citation Information

Patent Citations

  • Ceramic zirconium corundum grinding wheel

    CN103770028A

  • Resin metal composite mirror grinding wheel based on sol-gel method and preparation method of resin metal composite mirror grinding wheel

    CN110421494A